Nourishment, not restrictions - Managing obesity with food - Aktar, Yasmin (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Obesity is a multifaceted and complex condition that requires holistic management. Abnormal weight gain can occur in conjunction with a variety of physical, metabolic, and psychological health issues. Preventing obesity has received a lot of attention since it can help avoid conditions like type 2 diabetes mellitus (T2DM), hypertension, coronary heart disease, osteoarthritis, obstructive sleep apnea, reproductive issues, depression, and cancer. Obesity is often associated with weight stigma, impacting psychological well-being and quality of life. It is well documented how nutrition can impact our health and is important for all, regardless of body weight. However, eating patterns and macronutrient composition, as well as physical activity levels, have changed significantly. Urbanization and globalization have led to a trend toward greater portion sizes, increased consumption of fat and sugar, and rising prices for fresh produce and falling prices for processed foods. A calorie deficit of 500–600 kcal per day from the existing diet is recommended by conventional guidelines in a number of nations in order to lose 0.5–1 kg of weight per week. However, weight loss is not a direct linear trajectory and fluctuations can occur. It has been suggested that illnesses linked to obesity can be improved by losing 5–10% of body weight. In order to develop more effective strategies, it is important to understand the efficacy, health effects, and long-term sustainability of current dietary approaches to weight control. Improvements in diabetes and CVD risk factors have been observed with diets ranging from 10% fat to 45% fat. For weight loss, there is no "one-size-fits-all" diet; maintaining dietary modifications is the primary goal. It is essential to tailor the diet to each person's demands. The mix of dietary changes and physical exercise should be taken into account for both medication approaches and the weight maintenance phase. [J Assoc Clin Endocrinol Diabetol Bangladesh, 2025;4(Suppl 1): S18]